Analisis Kesalahan pada Penulisan Spanduk dan Beberapa Papan Nama - Nurfianawati, Freny; Ramdhani, Intan Sari (MASALIQ, 2022)
Banners or banners are print media used to present or disclose all existing data in any form. Basically, a banner is a stretched material containing essays and images that are usually circulated as a medium to raise an item to the community as a whole. Many non-standard words were found and errors were also found in the composition of the accentuation marks and these problems caused the writing to be inconsistent with the EYD. The main use of language is as a special device, as well as an instrument for exchanging messages with others. In today's circumstances, everyone is considered to communicate in a language because they can articulate the intended message. However, given the different circumstances of language, not all dialects are equally positive or negative, depending on the circumstances. The motivation behind this paper is to (1) describe the predominance of standard language use and accentuation among the general public. (2) Understand the improvements used in Indonesian and accentuation marks in accordance with the Indonesian spelling rules. The scientific technique used in this study uses subjective and observational strategies. There are several banners and billboards near the road that are used as a source of exam information. The findings of this study indicate that there are several bilingual sentences from different parts of spelling, style, accentuation, and sources.